Possibilities of Using Acoustic Materials in Open Plan Offices in Green Buildings - Ufuk Fatih Kucukali (Architecture Image Studies Scientific Journal)
One of the most important reasons for the increase in climate change in our world is buildings built based on old methods. In order to reduce the damages caused by the buildings to the environment, sustainable energy use, efficient use of resources, effective and long-term use of rainwater and natural light should be targeted. It is important for the materials used in green buildings to be recyclable in terms of reducing waste generation and supporting sustainable living. Technology, population growth, urbanization and the resulting work environments have also changed. The vast majority of work environments are designed as open offices due to the need for more employees and shared work areas other than closed offices. Open offices offer employees a more flexible work environment. Apart from the advantages of open offices, there are also disadvantages. The interventions to be made to solve the most important problem of noise have come to the fore. In open offices where noise is at a high level, it is aimed to reduce noise with decorative sound-absorbing acoustic materials covered on the wall partitions. In order to achieve this; ambient noise is reduced with acoustic materials used on the walls, ceiling and reinforcement elements. As a result, the prominent criteria and acoustic materials in the selection of acoustic partitions, acoustic ceilings and reinforcement elements in a green office were examined.